BOUNDEDNESS IN PERTURBED NONLINEAR FUNCTIONAL DIFFERENTIAL SYSTEMS - Choi, Sang Il; Goo, Yoon Hoe (Journal of the Chungcheong Mathematical Society, 2015)
In this paper, we investigate bounds for solutions of the perturbed nonlinear functional di®erential systems with a t1- similarity condition using the notion of h-stability. KCI Citation Count: 7